RIGIOLEPIS AND VACCINIUM (ERICACEAE) IN BORNEO - Argent, G. (Edinburgh Journal of Botany, 2018)
Rigiolepis and Vaccinium of Borneo are revised, and their characteristics are discussed. Brief comments on distinguishing Vaccinium and Rigiolepis from related genera in the Ericaceae are made. Vaccinium sect. Bracteata is now considered the only section of Vaccinium occurring in Borneo. The chief reason for reinstating Rigiolepis as a genus is the distinctive 10-locular ovary whose structure has been overlooked in recent studies, while the supporting characters of multiple axillary flower buds, flower size, anther shape and fruit colour provide for easy recognition. New keys are provided to all 42 species, and all accepted taxa are described. Ten taxa are new to science and 17 new combinations are made. An addendum gives the combinations to be used for the two species of Rigiolepis presently known to occur outside Borneo.